2019
DOI: 10.1007/s10147-018-01389-4
|View full text |Cite
|
Sign up to set email alerts
|

Three-year follow-up of a phase II study of radium-223 dichloride in Japanese patients with symptomatic castration-resistant prostate cancer and bone metastases

Abstract: Background Radium-223 is a first-in-class targeted alpha therapy to prolong overall survival (OS) in castration-resistant prostate cancer with bone metastases (mCRPC). The aim of the present analysis was to assess the long-term safety with radium-223 in Japanese patients with mCRPC. Methods Patients with symptomatic mCRPC, ≥ 2 bone metastases and no known visceral metastases received up to 6 injections of radium-223 (55 kBq/kg), one every 4 weeks. Adverse events (AEs) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 31 publications
2
9
1
Order By: Relevance
“…In the present analysis, we verified whether the prognostic power of the BIO-Ra score is still preserved in light of the EMA restriction of the use of Ra-223. Moreover, we verified the correlation between the BIO-Ra score and treatment completion, which is a well-known prognostic factor in mCRPC patients treated with Ra-223 [ 20 , 21 , 22 , 23 , 24 ].…”
Section: Introductionsupporting
confidence: 52%
See 1 more Smart Citation
“…In the present analysis, we verified whether the prognostic power of the BIO-Ra score is still preserved in light of the EMA restriction of the use of Ra-223. Moreover, we verified the correlation between the BIO-Ra score and treatment completion, which is a well-known prognostic factor in mCRPC patients treated with Ra-223 [ 20 , 21 , 22 , 23 , 24 ].…”
Section: Introductionsupporting
confidence: 52%
“…This finding is coherent with the observed prediction of treatment completion by the BIO-Ra score in the same time interval. Indeed, several previous studies showed a substantial survival benefit in patients reaching the completion of Ra-223 cycles [ 20 , 21 , 22 , 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Two UK and a single Canadian studies looked at the effect of completing at least five cycles of treatment and similar to our results, there was a survival benefit but at 5-9 months was less than the 25 months we found in our patient group. [ 16 17 18 ] The reason for this difference is unclear but maybe related to difference in patient selection at different treatment centers. For example, it was a policy in our region to refer patients for radium-223, if suitable, as soon as they failed chemical castration or chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…7 Although Ra-223 can play a major role in the management of mCRPC and symptomatic bone metastasis, it remains unclear how to best employ this treatment in clinical practice. 8,9 Some patients have disease progression of non-bone metastasis with eventually elevated PSA levels during Ra-223 treatment, which can occasionally be too late for the patient to receive subsequent therapies. Thus, the diagnostic certainty of bone-predominant mCRPC needs to be determined.…”
Section: Introductionmentioning
confidence: 99%